Bacterial-facilitated uranium transport in the presence of phytate at Savannah River Site. (May 2019) - Li, Runwei; Ibeanusi, Victor; Hoyle-Gardner, Jada; Crandall, Christy; Jagoe, Charles; Seaman, John; Anandhi, Aavudai; Chen, Gang
Abstract: At the Department of Energy (DOE) managed Savannah River Site (SRS), uranium and other heavy metals continue to pose threats to the ecosystem health and processes. In the oxic soil of this site, uranium is present primarily as soluble salts of the uranyl ion (i.e., U(VI) or UO2 2+ ). Although UO2 2+ has a strong sorption to the soil, the mobile indigenous bacteria may facilitate its transport. On the contrary, precipitation of UO2 2+ with phosphate has been found to be an alternative remediation strategy. This research investigated the effects of mobile bacteria and phytate on UO2 2+ transport at SRS in column experiments. It was discovered that UO2 2+ can barely be mobilized by de-ionized water but can be significantly transported with the aid of mobile indigenous bacteria. UO2 2+ had the most facilitated transport observation when it reached equilibrium with the bacteria before the transport. When UO2 2+ and bacterial were introduced to the soil at the same time or UO2 2+ was pre-deposited in the soil, the facilitated transport was less pronounced. In the presence of phytate, bacterial-facilitated UO2 2+ transport was hindered. pH was found to play the key role for UO2 2+ immobilization in the presence of phytate. The immobilization of UO2 2+ with the addition of phytate increased with the increase of pH within the pH range of this study because of the impact of pH on the solubility of UO2 (OH)2 . Phytate promoted UO2 - -PO4 3- complex and/or [Ca(UO2 )2 (PO4 )2 ] formation, leading to enhanced UO2 2+ immobilization in the SRS soil. Highlights: UO2 2+ transport was facilitated by indigenous bacterial strains at Savannah River Site (SRS). Facilitated UO2 2+ transport was highly affected by its interactions with the mobile indigenous bacteria. Phytate played an important role in UO2 2+ immobilization at Savannah River Site (SRS). Increase of pH enhanced UO2 2+ immobilization with phytate addition.